Long-term intake of soyabean phytosterols lowers serum TAG and NEFA concentrations, increases bile acid synthesis and protects against fatty liver development in dyslipidaemic hamsters. Issue 5 (14th September 2014) - Laos, Sirle; Caimari, Antoni; Crescenti, Anna; Lakkis, Jamileh; Puiggròs, Francesc; Arola, Lluís; del Bas, Josep Maria
<x content-type="archive" xml:space="preserve">Abstract</x> Various human trials and pre-clinical studies have suggested that dietary plant sterols possess hypotriacylglycerolaemic properties apart from their cholesterol-lowering properties. We hypothesised that phytosterols (PS) might attenuate triacylglycerolaemia by interfering with the deleterious effects of cholesterol overload in the liver. In the present study, twenty hamsters (Mesocricetus auratus) with diet-induced combined hyperlipidaemia were fed a high-fat diet (HFD, n 10) or a HFD supplemented with soyabean PS (n 10) for 40 d. In parallel, a healthy group was fed a standard diet (n 10). PS normalised fasting plasma cholesterol concentrations completely after 20 d and were also able to normalise serum TAG and NEFA concentrations after 40 d. HFD feeding caused microvesicular steatosis and impaired the expression of key genes related to fatty acid oxidation such as PPARA, carnitine palmitoyltransferase-Iα (CPT1A) and phosphoenolpyruvate carboxykinase 1 (PCK1) in the liver. PS treatment completely protected against HFD-induced steatosis and resulted in a normalised hepatic gene expression profile. The protection of the hepatic function by PS was paralleled by increased faecal cholesterol excretion along with a 2-fold increase in the biliary bile acid (BA):cholesterol ratio. The present study supports the conclusion that long-term consumption of PS can reduce serum TAG and NEFA concentrations and can protect against the development of fatty liver via different mechanisms, including the enhancement of BA synthesis. The results of the present study place these compounds as promising hepatoprotective agents against fatty liver and its derived pathologies.